Back to the future: revival, relevance and route of an anarchist/syndicalist approach for twenty-first-century left, labour and national liberation movements. Issue 3 (2nd July 2016) - van der Walt, Lucien
ABSTRACT: The failings of classical Marxism, social democracy and anti-imperialist nationalism point to the need for a radical left politics at a distance from the state. This paper examines the impact, revival and promise of the anarchist/syndicalist tradition, a rich, continuous praxis in labour, left, anti-imperialist, anti-racist and egalitarian movements, worldwide, since the 1860s. Outlining its core ideas – anti-hierarchy, anti-capitalism, anti-statism, opposition to social and economic inequality, internationalist class-based mobilisation – and critique of mainstream Marxism and nationalism, it highlights the arguments there is a basic incompatibility between state rule, and bottom-up, egalitarian, democratic, socialist relationships. The anarchist/syndicalist project cannot be reduced to an organising style, protest politics or spontaneism: for it, transition to a just, self-managed society requires organised popular capacity for a revolutionary rupture, developed through prefigurative, class-based, democratic organs of counter-power, including syndicalist unions aiming at collectivised property, and revolutionary counter-culture. Success needs formal organisation, unified strategy and anarchist / syndicalist political organisations.